Clinical Outcomes of Mild Isolated Cerebral Ventriculomegaly in the Presence of Other Neurodevelopmental Risk Factors. (1st November 2013) - Ball, John D.; Abuhamad, Alfred Z.; Mason, Janelle L.; Burket, Jessica; Katz, Elionora; Deutsch, Stephen I.
Abstract : Objectives: The purpose of this study was to evaluate neuropsychological test data in school‐aged children whose fetal sonograms revealed mild isolated cerebral ventriculomegaly without asymmetry of the lateral ventricles. Methods: Nine of 52 children 6 years and older with sonographic evidence of mild isolated cerebral ventriculomegaly without asymmetry of the lateral ventricles were able to be recruited for follow‐up school‐aged neuropsychological testing. The children received a half‐day battery of neuropsychological tests, including the Wechsler Abbreviated Scales of Intelligence; Beery‐Buktenica Developmental Test of Visual Motor Integration, Fifth Edition; Wide Range Achievement Test, Fourth Edition; and Integrated Visual and Auditory Continuous Performance Test. Parents completed the Conners 3 Parent Short Form and the Personality Inventory for Children, Second Edition. Results: In this small group, other risk factors for neurodevelopmental disorders were often present, including preterm birth, perinatal hypoxia, and a family history of psychiatric disease or substance abuse. Within this sample, the proportion of children with a pattern of test results showing poorer nonverbal intelligence than verbal intelligence scores and poorer math than reading performance, as well as meeting criteria for a diagnosis of attention deficit/hyperactivity disorder, was higher than the basal rates of these problems among children in general. Conclusions: Particularly given the complexity of various factors affecting neurodevelopment, follow‐up neuropsychological evaluation is warranted in children with sonographic evidence of mild isolated cerebral ventriculomegaly without asymmetry of the lateral ventricle (eg, in the context of poor school performance).